Theoretical and Experimental Investigation of Critical Buckling Load of Combined Columns - Hayder Zuhair Zainy; Aziz D. Almawash; Saddam K. Al-Raheem; Luay S. Al-Ansari; Mohammed Al-Edhari (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The work done in this research is dedicated to compute the critical buckling load of combined columns. This is performed using theoretical and experimental analyses. The combined column is made of two materials, namely copper and aluminum alloys. The theoretical approach involves numerical analysis using ANSYS and analytical analysis using the equivalent stiffness method. The study determines the critical buckling load by considering many parameters. These parameters include lengths of copper and aluminum in the combined columns, cross-sectional geometries (square, circle, and hexagon), and boundary conditions. The experimental work is carried out using a Strut Bucking Apparatus on a combined column with circular cross-sections and different end supports. The findings show that the critical buckling loads achieved from numerical and analytical analysis are in good agreement with those obtained from experimental analysis. It is found that the critical buckling load increases with increasing the length of copper in the combined column and with more restrictive end supports. There is a good match of critical buckling load between those achieved from the equivalent stiffness method and ANSYS model for any considered cross-sectional geometries (square, circle, and hexagon) and two types of support (fixed-fixed and fixed-pinned). The results reveal that the combined columns with square cross-sections have higher critical buckling loads than those with circular or hexagonal cross-sections. The highest percentage errors of critical buckling load between the experimental method and theoretical methods (equivalent stiffness method and ANSYS models) are (-13.120, -12.768, and -12.453) % and (-13.083, -18.039, and -19.052) % for pinned-pinned, fixed-pinned, and fixed-fixed columns respectively.